Engineering graphics - Giesecke, Frederick E. (Frederick Ernest), 1869-1953 (Harlow : Prentice Hall, 2003)
This authoritative text dominates the market by offering the best coverage of basic graphics principles and an unmatched set of fully machineable working drawings. Its practical, well illustrated, step-by-step explanations of procedures have successfully trained students for 60 years, and continue to appeal to today's visually oriented students.
The Graphic Language and Design -- Introduction to CAD -- Instrumental Drawing, Freehand Sketching, and Lettering Techniques -- Geometric Constructions -- Sketching and Shape Description -- Multiview Projection -- Sectional Views -- Auxiliary Views -- Revolutions -- Manufacturing Design and Processes -- Dimensioning -- Tolerancing -- Threads, Fasteners, and Springs -- Design and Working Drawings -- Reproduction and Control of Drawings -- Axonometric Projection -- Oblique Projection -- Perspective -- Points, Lines, and Planes -- Parallelism and Perpendicularity -- Intersections -- Developments -- Line and Plane Tangencies -- Cartography, Geology, and Spherical Geometry -- Graphical Vector Analysis.
Includes bibliographical references and index.
Previous ed.: 2000.
1
Keywords: Engineering graphics